The development of the Traffic Conflicts Technique: an approach to the study of road accidents - Lightburn, Angela D.C. (1984)
A practical and reliable alternative or supplement to injury accident data is necessary to diagnose dangerous sites and evaluate remedial measures because available accident data is scarce, is lacking in detail about the events preceding the accident and it takes a long time to accumulate statistically reliable data.